Evaluation of cervical screening at treatment of a vulvovaginal atrophy in periand postmenopausal women - T V Klinyshkova; I B Samosudova; O N Mironova (IP Berlin A.V., 2016)
Objective. Determination of effective application of vaginal complex estriol 0,2 mg/progesteron 2 mg/Lactobacillus casei rhamnosus 2¥109 at women with a vulvovaginal atrophy in peri-and postmenopausal women with a evaluation of cervical screening. Materials and methods. 109 patients with a vulvovaginal atrophy (VVA) were examined: the 1st group - 53 patients in a perimenopauza (middle age - 50.11±3.89 years), the 2nd group - 56 women in a postmenopause at the age of 65.8±4.13 years. The complex of researches included an assessment of complaints, the anamnestic and clinical data, bakterioskopic, cytologic and kolposkopic researches with interpretation of results according to the International standards and use of the modern equipment. The medical stage included vaginal application of a complex estriol, progesterone, L. casei rhamnosus on the 2nd capsules once a day during 14 (in the 1st group) and 21 day (in the 2nd group). Control of cervical cytologic inspection was carried out twice (in 4 and 6 weeks) after treatment. Conclusions. After the carried-out local therapy at patients of two groups clinical improvement of a current of VVA, normalization of a biocenosis of a vagina in comparison with basic data is established (p